Thermomechanical fatigue life prediction of 316L compact heat exchanger. (October 2016) - Laurent, M.; Estevez, R.; Fabrègue, D.; Ayax, E.
Abstract: Compact welded heat exchangers are designed to be used in severe operating conditions (temperature, pressure, aggressive fluid, etc.). Thus fatigue failure can be observed after large cyclic strain due to thermomechanical cyclic loads. In this paper, a 316L stainless steel structure solicited in the (extremely) low cycle fatigue regime is analyzed through a multi-scale approach. A finite element analysis method has been developed and correlated to experiments. The thermo-elastic response of the heat exchanger to thermal cycling of various amplitudes has been firstly investigated. The stress concentration locations are identified and the local thermo-elastic stored energy on these points is calculated. By the use of a combined isotropic/kinematic hardening previously determined by alternated bending tests, these data are then used in a micromechanic approach. It consists in the consideration of the material elastic-plastic behavior under uniaxial mechanical solicitation. Based on energy equivalence, a local nonlinear description is so adopted to an expected equivalent strain amplitude. This estimation is used to predict the lifetime of the heat exchangers through an adapted rule relying this deformation to cycle number to failure through the Coffin Manson law. The methodology, simple to handle, is thought to improve the design of heat exchangers depending on their operating conditions. Highlights: A finite element model of a large heat exchanger is built. Elastic calculations are carried out to find the stress concentration zones. An equivalence of elastic energy and plastic one is used in these zones to calculate plastic strain. The behavior and the fracture criterion are determined on independent experiments. An accurate prediction of the fatigue life of real heat exchanger is possible thanks to this strategy.